The Influence of Gestational Age on Neonatal Hypoglycemia Among Preterm Neonates in Secondary Hospital Setting - Mastuti, Ni Luh Putu Herli (Majalah Kesehatan Indonesia, 2025)
Preterm neonates frequently encounter health challenges due to immaturity of organ systems, particularly metabolic complications such as hypoglycemia. This study aimed to analyze gestational age as a risk factor for neonatal hypoglycemia in a secondary hospital setting. An observational retrospective design was employed using medical records of preterm neonates born before 37 weeks gestation, admitted to Mitra Delima Hospital, Malang, Indonesia, between January and December 2023. Neonates with diabetic mothers or congenital anomalies were excluded. Hypoglycemia was defined as blood glucose levels below 60 mg/dL measured via heel puncture. Of 59 preterm neonates studied, 17 (29%) experienced hypoglycemia, while 42 (71%) maintained normoglycemia. Cesarean section deliveries accounted for 74.6% of the cases, with no significant differences in maternal age or neonatal complications between groups. Gestational age was significantly lower in hypoglycemic neonates compared to those normoglycemic (mean 24.18 vs. 33.93 weeks; p=0.045), although birth weight alone did not significantly correlate with hypoglycemia. These findings suggest that lower gestational age constitutes a primary risk factor for neonatal hypoglycemia. Thus, rigorous clinical monitoring and targeted screening protocols are strongly recommended, especially for neonates born prematurely, to mitigate hypoglycemia-related morbidity and long-term neurodevelopmental complications.